Path Analysis of Recording and Reporting the Maternal and Child Health (MCH) Cohort Register at Ardimulyo Health Center - Endang Yuliani; Retno Dewi Prisusanti (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
According to data from the Maternal Perinatal Death Notification (MPDN), the maternal death recording system of the Ministry of Health, the number of maternal deaths increased from 4,005 cases in 2022 to 4,129 cases in 2023. The objectives of this research are:Identify Variable Relationships: To assess how staff training, technology usage, and data integration affect the accuracy and efficiency of recording and reporting.Evaluate Direct and Indirect Effects: To analyze the direct and indirect impacts of these variables on the outcomes of the recording and reporting system. Provide Improvement Recommendations: To develop recommendations for enhancing the recording and reporting system based on the analysis results. Research Methodology Path analysis is required to evaluate the relationships between various factors that influence the recording and reporting system.Steps in Path Analysis: Data Collection, Path Analysis Model, Statistical Analysis, Interpretation of Results. Staff Training (X1): Data Accuracy (Y1): β = 0.45 (p < 0.01).Reporting Efficiency (Y2): β = 0.40 (p < 0.05), Technology Usage (X2):Data Accuracy (Y1): β = 0.35 (p < 0.05)Reporting Efficiency (Y2): β = 0.55 (p < 0.01), Data Integration (X3):Data Accuracy (Y1): β = 0.50 (p < 0.01), Reporting Efficiency (Y2): β = 0.45 (p < 0.01). Path analysis reveals that staff training, technology usage, and data integration have a significant impact on the recording and reporting system at Ardimulyo Health Center. Improvements in these three variables can enhance the accuracy and efficiency of reporting. Recommendations for improvement include investing in staff training, implementing better technology, and enhancing data integration.